HDL Subclass Distribution Shifts with Increasing Central Adiposity - Nicholas J. Woudberg; Sandrine Lecour; Julia H. Goedecke (Journal of Obesity)
Although cross-sectional studies have shown that obesity is associated with lower concentrations of large high-density lipoprotein (HDL) subclasses, it is unknown if changes in HDL subclasses are related to changes in body fat and its distribution over time. We therefore assessed changes in HDL subclass distribution over a 5.5-year free-living follow-up period in 24 black South African women. At baseline and follow-up, body composition and body fat distribution were measured using anthropometry, dual X-ray absorptiometry, and computerized tomography. HDL subclass distribution was quantified using Lipoprint®. Over the 5.5-year follow-up period, body fat (+17.3 ± 4.5 kg, p<0.05) and trunk fat mass (+7.4 ± 1.9%, % fat mass, FM, p<0.05) increased, while leg fat mass (−2.53 ± 0.56%, % FM, p<0.001) and the distribution of large (−6.43 ± 2.12%, p<0.05) HDL subclasses decreased. A percentage decrease in large HDL subclasses was associated with a percentage increase in central fat mass (visceral adipose tissue (VAT) area, p<0.05) and a percentage decrease in peripheral fat mass (leg fat mass). These preliminary findings suggest that a relative redistribution of body fat from the periphery to the abdominal region were associated with a decrease HDL subclass size in black South African women and provide a novel link between body fat distribution and lipidology in this population.